PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS V - Sri Cacik; Meilia Ika Nur Irdana (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2017)
This study aims to describe the improvement of student learning outcomes, teacher activities, and student activities and student’s responses to science learning using CTL model with natural media in class V SDN Gunungrejo 1. The results showed that the learning outcomes in cycle I obtained an average score of 70.5, cycle II 76.4, cycle III 83. Percentage mastery learning cycle I was 43%, cycle II 81%, and 95% 95% cycle. Presentation of teacher activity in cycle I 65%, cycle II 76%, and cycle III 83%. Presentation of student activity in cycle I 61%, cycle II 70%, and cycle III 83%, and students respond positively to science learning using CTL model with natural media. This is proven by the percentage obtained that many students who answered "yes" amounted to 87.6%. Thus, the use of CTL model can improve student's learning result, teacher activity, and student activity.